Sustainable Production and Consumption: A New Trend in the Fashion Industry - Hoa, Nguyen Thi Kim (Advances in Social Sciences Research Journal, 2026)
Sustainable fashion is not just a trend, but a call to action, a philosophy of responsible living. By understanding and applying these principles, we not only beautify ourselves but also contribute to protecting the planet and building a better future for next generations. In this article, the author analyzes the trends in the use of recycled materials in the textile and fashion industry worldwide, and in Vietnam specifically. Based on this analysis, the author provides insights, assessments, and proposes solutions for the sustainable development of the garment industry in the future.